EDUCATIONAL STORY BOOK BASED ON TOLERANCE CHARACTER AS AN INNOVATION OF INTRODUCING MULTICULTURAL EDUCATION - Fatmawati, Laila; Khotijah, Ayu Siti; Erviana, Vera Yuli (Universitas Negeri Semarang, 2018)
Multicultural education is still very foreign to elementary school teachers and students. Need innovation in introducing multicultural education to elementary school students through educational story book. The aims of this study are: 1) developing educational story book based on tolerance character, 2) knowing the feasibility of the educational story book based on experts’ judgment, 3) knowing the responses of teachers and students after using educational story book. The development procedure adopted Borg and Gall model. Data collection techniques were questionnaires and interviews. Data analysis techniques was descriptive statistics and qualitative analysis of interactive model. Small group trial subject used six students in the 5th grade of Wirosaban Elementary School. While the large group trial used 20 students in the 5th grade of Pakel Elementary School. The results of the study are educational story book with the title